"The Role of Sense of Coherence and Proactive Coping in Enhancing Quality of Life: A Statistical Analysis" - Dr. Mansi Yadav*, Dr. Shailendra Singh** (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The present study explores the role of Sense of Coherence (SOC) and Proactive Coping in enhancing individuals’ quality of life (QoL). Both SOC and proactive coping have been identified as key factors that contribute to psychological resilience and well-being, especially in the face of stressors. This statistical analysis investigates the relationship between these constructs and their combined impact on quality of life among young adults. The results suggest that individuals with a higher Sense of Coherence and a greater use of proactive coping strategies reported significantly better quality of life outcomes, including higher levels of life satisfaction, emotional well-being, and personal growth. These findings underline the importance of fostering SOC and proactive coping as part of psychological interventions aimed at improving overall quality of life.